Predictors and Contexts of Unsolved and Solved Sexual Offenses. (August 2020) - Chiu, Yi-Ning; Leclerc, Benoit
Drawing from perspectives emphasizing environmental crime event components, this study identifies the predictors and contexts of unsolved and solved sexual offenses against women by strangers. Police data were obtained from 542 cases in Queensland. Hierarchical logistical regression was adopted to analyze variables relating to situational, contextual, and offender–victim interaction elements. Common contexts were examined using conjunctive analysis. Cases were significantly likely to remain unsolved if the offender used minimal force, or if the victim was walking outside at the time of initial contact. Conversely, solved cases were significantly associated with offender prior consumption of alcohol/drugs, bystander presence, and vehicle use. Crimes with higher criminal "effectiveness" and lower levels of victim interaction tended to be associated with unsolved sexual offenses.